Antioxidant Potential and Active Compound Identification of Hylocereus costaricensis and Hylocereus undatus Peel Extracts using LC-MS/MS - Mulyati, Ade Heri; Nurmayani, Reni; Widiastuti, Diana; Warnasih, Siti; Sinaga, Siska Elisahbet (Chimica et Natura Acta, 2025)
The object of this research was to determine the antioxidant potential and identify active compounds in the peel extracts of red dragon fruit (Hylocereus costaricensis) and white dragon fruit (Hylocereus undatus). Phytochemical tests were conducted to identify flavonoids, alkaloids, tannins, coumarins, and saponins. The antioxidant activity was assessed using the DPPH assay, while vitamin C content was quantified using UV-Vis spectrophotometry, and bioactive antioxidant compounds were identified through LC-MS/MS spectrophotometry. The results demonstrated that phytochemical screening revealed the presence of flavonoids and alkaloids in both extracts. Antioxidant activity assays indicated that the red dragon fruit peel extract exhibited an IC50 of 32.7 ppm (very active), while the white dragon fruit peel extract had an IC50 of 50.2 ppm (active), with the vitamin C control showing an IC50 of 11.90 ppm. The red dragon fruit peel extract had the highest vitamin C content (1.45%) compared to the white dragon fruit peel (1.04%). LC-MS/MS analysis identified several organic compounds, including the flavonoid isoliquiritigenin and alkaloid compounds such as aporphine, melosmine, 3-carbamoyl-1-(2-deoxy-beta-D-erythro-pentofuranosyl)-4,5-dimethylpyridinium, and alkaloid group (6-Amino-5-{[2(diethylamino) ethyl]amino}-1-propyl -2,4(1H,3H)-pyrimidinedione). These findings suggest that both red and white dragon fruit peel extracts possess significant antioxidant potential, with red dragon fruit peel demonstrating superior activity. This study can be used for further research on food technology in producing food products that are rich in nutrients.